(untitled) (Al-Aasar, 2025)
The rapid diffusion of digital platforms has intensified the spread of misinformation in developing countries, where high mobile penetration intersects with low levels of trust in institutions and uneven media literacy. This paper examines how citizens in developing countries respond to online news, with particular focus on misinformation, fact-checking initiatives, and media literacy. Drawing on the information disorder framework, inoculation theory, and dual-process models of persuasion, the study develops and tests a model linking media literacy, trust in fact-checking, and news consumption patterns to behavioral responses such as sharing, verification, and avoidance of online news. Using a cross-sectional survey of 1,200 respondents from three developing countries (Pakistan, Nigeria, and Brazil), combined with an embedded vignette experiment presenting false and fact-checked news items, the study finds that higher media literacy is associated with lower likelihood of sharing unverified content and greater willingness to consult fact-checking sources. Exposure to fact-checks and trust in fact-checking organizations significantly increase verification behaviors but do not entirely prevent the sharing of sensational misinformation. The findings highlight structural constraints—such as platform design, messaging apps, and political polarization—that limit the impact of fact-checking alone. The paper argues that coordinated strategies combining media literacy education, platform governance, and locally rooted fact-checking ecosystems are crucial for strengthening resilience to misinformation in the Global South.